H-103 Towards a universal influenza virus vaccine. (April 2018) - Palese, Peter
Abstract : Despite FDA-approved vaccines and antivirals, seasonal and pandemic influenza remains a serious threat associated with substantial morbidity and mortality. While annual seasonal influenza virus vaccination is frequently effective–albeit underutilized in most countries–a safe universal influenza virus vaccine providing broad and long-lasting immunity would represent a major breakthrough. We have developed vaccine constructs which express chimeric hemagglutinins resulting in the redirection of the immune response away from the immunodominant (variant) head domain of the hemagglutinin toward the much more conserved stalk of the hemagglutinin and the highly conserved neuraminidase. Such vaccine constructs work well in animal challenge models and await extensive clinical trials in humans. The mechanism by which these novel vaccines mediate protection is via antibodies which do not rely on hemagglutination inhibitory (HI) activity but rather on ADCC (antibody-dependent cell-mediated cytotoxicity) effects, activation of complement and/or inhibition of virus replication through directly binding to viral proteins. It is hoped that the universal influenza virus vaccine based on chimeric hemagglutinins will provide long-lasting protection against all seasonal and pandemic influenza virus strains in the future with the possibility of eventually eliminating influenza B.